Through the Wall Human Subject Localization and Respiration Rate Detection using Multichannel Doppler Radar - Harikesh; Chauhan, Shakti Singh; Basu, Ananjan; Abegaonkar, Mahesh P.; Koul, Shiban Kishen (IEEE sensors journal, 2021)
In this paper, through-the-wall human subject localization and respiration rate detection using a multi-channel Doppler radar is proposed. The proposed methodology is used to detect respiration signal of the subject when the environment between the radar and the subject is wood, glass or any other material which resembles real-life situations. A major achievement is that angular position of multiple human subjects and their respiration rates are estimated using this technique. The proposed system also removes the null point detection problem which is present in single channel CW radar system for vital sign detection. The noise level is reduced using cross-correlation between received signals from different channels. Also, the received signals from different channels are added in phase to improve the detection. The system is compact enough to be carried on a micro-drone. This work finds application in real-life situations such as earthquake, medical-care, building collapse and patient monitoring.